BIOMASS AND PRODUCTIVITY OF WEEDS IN A FALLOW PERIOD AT GUJAR TAL MARGIN - Singh, Mayank; Singh, O. P.; Singh, M. P. (Ecoprint: An International Journal of Ecology, 2014)
This paper deals with biomass accumulation and net primary productivity pattern in a fallow period of a lake margin agroecosystem. The slight slopping margin of present study site was characterized into two ecological zones, i.e. upper and lower from top up-land to lower region near water margin. Maximum biomass of dominant weed Cynodon dactylon (Linn.) Pers. and ‘rest weeds’ were 190.55 and 265.22 g m-2 in upper zone in September. In contrast, in the lower zone of study site peak value of biomass of dominant plant C. dactylon and ‘rest weeds’ were 67.91 and 178.84 g m-2, respectively in June as lower zone was inundated from fist fortnight of July to September, 2008. The Maximum percentage contribution of dominant weed (C. dactylon) was 54.00 and 59.15% in March and ‘rest weeds’ was 74.49 and 75.15% in April, 2008 in the respective upper and lower zones. Maximum productivity values of respective dominant weed (C. dactylon) and ‘rest weeds’ in upper zone were 2.07 and 2.51 g m-2 day-1 in July. In contrast, in the lower zone of the study site the peak productivity values of respective dominant weed (C. dactylon) and ‘rest weeds’ were observed 1.36 in June and 1.23 g m-2 day-1 in October. Total productivity values in two respective zones upper and lower have varied 330.59 and 140.17 g m-2 per eight month. Analysis of variance in standing biomass of plant species was found significant (p<0.05 in upper zone and p<0.01 in lower zone). DOI: http://dx.doi.org/10.3126/eco.v19i0.9858 Ecoprint An International Journal of Ecology Vol. 19, 2012 Page: 85-90 Uploaded date: 2/14/2014